Víctor Andrés Belaunde: anti-modern or ultramodern? - Masías Vergara, Carlos (Mercurio Peruano, 2018)
The author reflects on three positions against modernity which are highlighted in Belaunde’s thought. He has been considered an author contrary to modernity for a long time. He is a reactionary conservative person as a result of his conversion to Catholicism; however, this view is distorting because the truth is that he could be situated within a trend of modern tradition. Belaunde judges modernity from a metaphysical view of reality, from which the critique of modern reason and the search for otherness is explained. The criticism of modernity is not something of recent times but since its beginning, the modern project was the subject of criticism and position taken from within its own dynamism. The rebellion of modernity has consisted, for Belaunde, in denying the spiritual dimension of reality. But this denial has not been made explicitly, but by the subtle way of confusing the spirit with matter or life. But Belaunde does not propose a return to medievality or a new form of Old Regime. Belaunde believes that the spiritual force of Christianity can again raise a new civilization, and in that sense his critique of modernity is an attempt to overcome it, to go beyond it. Belaunde is an ultramodern person.